2022
DOI: 10.1101/2022.12.14.520481
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Repetition accelerates neural markers of memory consolidation

Abstract: No sooner is an experience over than its neural memory representation begins to be strengthened and transformed through the process of memory replay. Using fMRI, we examined how memory strength manipulated through repetition during encoding modulates post-encoding replay in humans. Results revealed that repetition did not increase replay frequency in the hippocampus. However, replay in cortical regions and hippocampal-cortical coordinated replay were significantly enhanced for repeated events, suggesting that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 106 publications
(169 reference statements)
0
8
0
Order By: Relevance
“…Of note is that during learning, YC conducted more learning cycles and received repeated feedback about the correct location. Therefore, the continual improvement and updating of their performance may have led to more stabilized and resistant to decay memory precision (MacLeod et al, 2018), despite lower levels of retained details (McDermott & Zerr, 2019; Yu et al, 2022). On the other hand, higher number of initially retained details reflected in higher initial memory precision in YA could provide more opportunities for the information’s quality decay.…”
Section: Discussionmentioning
confidence: 99%
“…Of note is that during learning, YC conducted more learning cycles and received repeated feedback about the correct location. Therefore, the continual improvement and updating of their performance may have led to more stabilized and resistant to decay memory precision (MacLeod et al, 2018), despite lower levels of retained details (McDermott & Zerr, 2019; Yu et al, 2022). On the other hand, higher number of initially retained details reflected in higher initial memory precision in YA could provide more opportunities for the information’s quality decay.…”
Section: Discussionmentioning
confidence: 99%
“…Analyses of remote > recent difference in neural activation over time allowed us to control for the effects of rapid consolidation during repeated learning, examining changes in short-or long-delay neural activation relative to immediate retrieval activation (Brodt et al, 2016a(Brodt et al, , 2018Yu et al, 2022 ). First, we observed increased activation in the vlPFC over time in both age groups, while overall vlPFC activation was higher in young adults.…”
Section: Differential Upregulation Of Remote > Recent Neural Activati...mentioning
confidence: 76%
“…For instance, in young adults, repeated exposure to word-image pairs during encoding, compared to single exposure, was shown to accelerate memory consolidation. This is achieved through enhanced replay of repeated events in the retrosplenial cortex (RSC) and the medial prefrontal cortex (PFC), as well as via increased hippocampal (HC)-cortical replay that promotes the associative word-object memories (Yu et al, 2022 ). In another study by , it was found that during repeated spatial navigation in a virtual environment, activation in the posterior parietal cortex (PPC), especially the precuneus, increased and remained elevated after 24 hours, while HC activity and HC-PPC connectivity declined with repeated encoding rounds .…”
Section: Neural Correlates Of Memory Consolidationmentioning
confidence: 99%
“…Analyses of neural upregulation (i.e., remote > recent difference in neural activation) over time allowed us to control for the effects of rapid consolidation during repeated learning, while examining changes in short- or long-delay neural activation (Brodt et al, 2016b, 2018; Yu et al, 2022). First, we observed increased upregulation in the vlPFC over time in both age groups, with vlPFC upregulation being higher in young adults.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in young adults, repeated exposure to word-image pairs during encoding, compared to single exposure, was shown to accelerate memory consolidation. This is achieved through enhanced replay of repeated events in the retrosplenial cortex (RSC) and the medial prefrontal cortex (PFC), as well as via increased hippocampal (HC)-cortical replay that promotes the associative word-object memories (Yu et al, 2022). In another study by Brodt et al (2016), it was found that during repeated spatial navigation in a virtual environment, activation in the posterior parietal cortex (PPC), especially the precuneus, increased and remained elevated after 24 hours, while HC activity and HC-PPC connectivity declined with repeated encoding rounds (Brodt et al, 2016).…”
Section: Introductionmentioning
confidence: 99%